Profile of an occupation – medical assistant - Schambeck, Arne [Verfasser] (My University, 2025)
No doctor’s surgery is able to do without them. Medical assistants perform some of the most varied tasks in any of the medical professions. They look after patients and assist with examinations, treatments and operational organisation. Social competencies are also becoming increasingly relevant. This occupational profile describes why this is the case and provides current training figures. (BIBB-Doku)
Keywords: S 6.4.5.2 Übrige Gesundheitsberufe (außer Ärzte und Apotheker); 370; Medizinischer Fachangestellter; Tätigkeitsmerkmal; Berufsbild; Sozialkompetenz